The competitiveness study on Kelantan paddy industry using porter's diamond model / Azmahani Yaacob@Othman , Prof Dr Zulkornain Yusop and Syazwani A Malek @ Abdul Malek - Yaacob@Othman, Azmahani; Yusop, Zulkornain; A Malek@Abdul Malek, Syazwani (Universiti Teknologi MARA Kelantan, 2019)
This study used the Porter’s Diamond Model as the theoretical underpinning to examine the competitiveness of Kelantan paddy industry. The model examined six (6) factors that were factor conditions, demand conditions, farmers’ strategies and supporting industries, chances and government’s roles. A total of 344 farmers were involved in this study. The farmers were required to answer a set of questionnaires which were adopted and customized from previous study. Partial least Square (PLS) SmartPLS M2 Version 3.0 was used for data analysis. The result showed that only four variables were significant and able to explain the competitiveness of paddy industry in Kelantan. They were factor conditions, demand conditions supporting industries and chances.